Interview with Prof. Klippies Kritzinger - M. Laubscher (Acta Theologica)
J.N.J. (Klippies) Kritzinger is an emeritus professor of Missiology at the University of South Africa (Unisa).  Martin Laubscher interviewed him on his contribution to Theology.